The Modern Spirit of Asia: The Spiritual and Secular in China and India, by Peter van der Veer - Theodor, Ithamar (Religions of South Asia, 2015)
The Modern Spirit of Asia: The Spiritual and Secular in China and India, by Peter van der Veer. Princeton, NJ and Oxford: Princeton University Press, 2014. xi + 282 pp. £52.00. ISBN 978-0-691-12814-6 (hardback). £16.95. ISBN 978-0-691-12815-3 (paperback).